In search of true monarchy : Montesquieu, Speranskii, Karamzin and the politics of reform in early nineteenth-century Russia - Taki, Victor (2009)
In search of true monarchy : Montesquieu, Speranskii, Karamzin and the politics of reform in early nineteenth-century Russia (2009) 22 février 2013, par Taki, Victor European review of history, 16, 1 (2009), p. 125-149.
Keywords: exportSPIP